A Study of Meaning and Messages With Reference to the Novel Rage of Angel - Sudiarta Putri, Ni Made Devi; Sukarini, Ni Wayan; Savitri, Putu Weddha (Humanis, 2021)
This study was aimed to identify and analyze the meaning and message in several sentences found in the novel Rage of Angels by Sidney Sheldon published in 1980. The selected sentences in the novel, which are the data of this study, were collected by applying the documentation method and note-taking technique which then were analyzed using the descriptive qualitative method. The data were presented informally in descriptive form. This study analyzes the types of meaning based on the theory proposed by Leech (1974) and the messages of the novel based on the biographical approach theory by Wellek and Warren (1962). As a result, all the seven types of meaning, namely connotative meaning, conceptual meaning, affective meaning, stylistic meaning, reflected meaning, collocative meaning, and thematic meaning, were found in the novel. In relation to the message of the novel, based on the biographical approach, there were five messages that the author delivered.